Impact of the war in Ukraine on nuclear waste management in arctic Russia - Gladkov, Sergei (Finland, 2026)
The objective of this report is to identify the changes that have occurred in the system of nuclear waste management in the Arctic territories of Russia. It is impossible to overstate the importance of the Arctic in the modern era. The economic, climatic, environmental and safety aspects of the Arctic are attracting increased attention from a variety of stakeholders. In considering the issues of radioactive waste management in Russia, it is essential to recon with the multicomponent nature of the nuclear power complex and the presence of a considerable number of nuclear legacy sites. The Russian nuclear industry, comprising both civilian and military operations, has amassed a considerable quantity of nuclear waste. A considerable proportion of this waste has accumulated in the Russian Arctic region, including on the seabed of the Arctic Ocean and its associated seas. Following the dissolution of the USSR, the Russian government has been engaged in the construction of a system for the management and ultimate elimination of radioactive waste and other issues related to the so-called ‘nuclear legacy’ for an extended period of time. International cooperation played a pivotal role in the development of this system. Foreign states provided substantial financial and technological assistance within the framework of various international structures. However, following the outbreak of the war in Ukraine, these ties were abruptly severed. Russia is now prioritizing economic projects for the utilization of nuclear energy in the Arctic, while environmental considerations have been largely overlooked. This approach poses a significant risk to the delicate ecological balance in the Arctic.